2023
DOI: 10.3390/ijfs11010027
|View full text |Cite
|
Sign up to set email alerts
|

Maize Productivity and Household Welfare Impacts of Mobile Money Usage in Tanzania

Abstract: This study examined the determinants and impacts of mobile money (MM) usage on maize productivity and poverty likelihood (i.e., the probability of a household falling below the international poverty line at USD 1.9 per capita per day) in the Mbeya Region, Tanzania. The analysis was conducted using the endogenous switching regression (ESR) model on data from a random sample of 1310 households selected from seven districts in the region. Results of the ESR estimation show that MM usage is strongly and positively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Studies (Kumar et al, 2022;He et al, 2021;Ireri et al, 2021;Victor et al, 2021;Munyua, 2021) have shown that culture can either support or hinder mobile phone usage awareness and differs across societies in different countries. In Tanzania, studies (Iddi et al, 2023;Kilombele et al, 2023;Kinyashi et al, 2022;Magesa and Mkasanga, 2021;Benard et al, 2020) have mainly focused on accessing business information, farmers' welfare, perceived usefulness and challenges. However, few studies (Summers et al, 2020 andMtega andNgoepe, 2019) on culture and mobile phone revealed that husbands decided on mobile phone ownership and use for married women.…”
Section: Introductionmentioning
confidence: 99%
“…Studies (Kumar et al, 2022;He et al, 2021;Ireri et al, 2021;Victor et al, 2021;Munyua, 2021) have shown that culture can either support or hinder mobile phone usage awareness and differs across societies in different countries. In Tanzania, studies (Iddi et al, 2023;Kilombele et al, 2023;Kinyashi et al, 2022;Magesa and Mkasanga, 2021;Benard et al, 2020) have mainly focused on accessing business information, farmers' welfare, perceived usefulness and challenges. However, few studies (Summers et al, 2020 andMtega andNgoepe, 2019) on culture and mobile phone revealed that husbands decided on mobile phone ownership and use for married women.…”
Section: Introductionmentioning
confidence: 99%